Wednesday

March 4, 2015

March 4, 2015

Posted by **Kathryn** on Wednesday, September 22, 2010 at 12:04pm.

- 12th grade -
**MathMate**, Wednesday, September 22, 2010 at 12:09pmHint:

(1-x^n) = (1-x)(1+x+x²+x³+...+x^{n-1})

**Answer this Question**

**Related Questions**

Math - Prove that the statement: (1/5)+(1/5^2)+(1/5^3)+...+(1/5^n)=(1/4)(1-1/5^n...

Algebra II - The problem is:Prove that the statement 1/5+1/5^2+1/5^3+...1/5^n=1/...

Algebra II - The problem is:Prove that the statement 1/5+1/5^2+1/5^3+...1/5^n=1/...

Algebra II - In an induction proof of the statement 4+7+10+...+(3n-1)=n(3n+5)/2 ...

math - 1)Find the third iterate x3 of f(x)=x2-4 for an initial value of x0=2 A)-...

discrete math - use a direct proof to show that the product of two odd numbers ...

math induction - prove the product of 4 consecutive integers is always divisible...

discrete math - 1)prove that if x is rational and x not equal to 0, then 1/x is ...

Mathematical induction. I'm stuck. So far I have.. - For all integers n ≥ ...

math - Let f:ℤ+ → ℤ+ be the function defined by: for each x &#...